Transfer free graphene growth on SiO2 subsrate at 250oC - Vishwakarma, Riteshkumar; Rosmi, Mohamad Saufi; Takahashi, Kazunari; Wakamatsu, Yuji; Yaakob, Yazid; Ibrahim Araby, Mona; Kalita, Golap; Kitazawa, Masashi; Tanemura, Masaki (Nature Publishing Group, 2017)
Low-temperature growth, as well as the transfer free growth on substrates, is the major concern of graphene research for its practical applications. Here we propose a simple method to achieve the transfer free graphene growth on SiO2 covered Si (SiO2/Si) substrate at 250 °C based on a solid-liquid-solid reaction. The key to this approach is the catalyst metal, which is not popular for graphene growth by chemical vapor deposition. A catalyst metal film of 500 nm thick was deposited onto an amorphous C (50 nm thick) coated SiO2/Si substrate. The sample was then annealed at 250 °C under vacuum condition. Raman spectra measured after the removal of the catalyst by chemical etching showed intense G and 2D peaks together with a small D and intense SiO2 related peaks, confirming the transfer free growth of multilayer graphene on SiO2/Si. The domain size of the graphene confirmed by optical microscope and atomic force microscope was about 5 μm in an average. Thus, this approach will open up a new route for transfer free graphene growth at low temperatures.